Dynamic population pharmacokinetic–pharmacodynamic modelling and simulation supports similar efficacy in glycosylated haemoglobin response with once or twice‐daily dosing of canagliflozin. (31st January 2017) - de Winter, Willem; Dunne, Adrian; de Trixhe, Xavier Woot; Devineni, Damayanthi; Hsu, Chyi‐Hung; Pinheiro, Jose; Polidori, David
Abstract : Aim: Canagliflozin is an SGLT2 inhibitor approved for the treatment of type‐2 diabetes. A dynamic population pharmacokinetic–pharmacodynamic (PK/PD) model relating 24‐h canagliflozin exposure profiles to effects on glycosylated haemoglobin was developed to compare the efficacy of once‐daily and twice‐daily dosing. Methods: Data from two clinical studies, one with once‐daily, and the other with twice‐daily dosing of canagliflozin as add‐on to metformin were used ( n = 1347). An established population PK model was used to predict full 24‐h profiles from measured trough concentrations and/or baseline covariates. The dynamic PK/PD model incorporated an E max relationship between 24‐h canagliflozin exposure and HbA1c‐lowering with baseline HbA1c affecting the efficacy. Results: Internal and external model validation demonstrated that the model adequately predicted HbA1c‐lowering for canagliflozin once‐daily and twice‐daily dosing regimens. The differences in HbA1c reduction between the twice‐daily and daily mean profiles were minimal (at most 0.023% for 100 mg total daily dose [TDD] and 0.011% for 300 mg TDD, up to week 26, increasing with time and decreasing with TDD) and not considered clinically meaningful. Conclusions: Simulations using this model demonstrated the absence of clinically meaningful between‐regimen differences in efficacy, supported the regulatory approval of a canagliflozin‐metformin immediate release fixed‐dose combination tablet and alleviated the need for an additional clinical study.